ADVENTURE, GAME AND MAZINESS IN IMAGINARY SOCIAL OF YOUTH GAME PLAYER FANS FOR DIGITAL CONTROL STRIKE (Fiep Bulletin - online, 2011)
The forms of entertainment for young people were transformed into e-culture, networks that launch them into a systematic life differently, leading them to conditions such as sedentary lifestyles. The evidence suggests that factors specific to the game are present in digital games: the players relation with himself, with his colleagues and with the games, rituals before matches and in training, concerns about food, sleep and the body's health, bullying opponents, veneration and disqualifications of individuals, superstitions and dreams of becoming the best at what they do. The complexity of virtual reality imposes the profession of physical education a world full of uncertainty, which requires the transmission of knowledge, in a character of permanent training of young people. Faced with the challenge of change, to motivate, to produce a reflexive capacity that conforms to the current context, we investigated the sense of adventure, game, and maziness present in the social imagination of young fans of the game Counter Strike (CS), also diagnosed how the solidarities animate, the differences and similarities between the speeches' sense of these players (as). The qualitative study, under the methodology of the social imaginary focuses on the reaction's sense of the fans of CS in the adventure dimensions of subjectivity, game, and maziness. CS is one of the most popular computer games online. This is a duel game based on rounds of shots in which teams of counter-terrorists versus terrorists face to victory. This is a game of almost perfect simulation of reality in which the adventure is presented in the game maziness experience of the phases' challenges. In addition to the categories of agon and mimicry, also ilynx enshrine the hidden power of the characters of the games.
Keywords: adventure; digital games; play; maziness